Subtitling Strategies of Taboo Words in "Sex Education TV Series Season 2" - Rafika Zahra; Sujana Sujana (JEdu: Journal of English Education, 2022)
This research aims to identify the types of taboo words, to identify the functions of taboo, and to observe the subtitling strategy in the translation of taboo words in Indonesian subtitles in Sex Education Season 2 TV Series. The source of data in this research is the dialogue that contained taboo words in the English subtitle and the Indonesian subtitle script in the Sex Education TV Series season 2. The researcher uses the descriptive qualitative method. The first result of this study show there were 201 data can be classified as types of taboo words where the highest type is sexual activity 70 data (35%), and the lowest type is lavatory 38 data (19%). The second result shows the 201 data can be categorized as a function of taboo words where the highest type is surprise 60 data (30%), and the lowest type is joking 15 data (8%). The most common use of sexual activity taboo words is to express anger and/or frustration. Furthermore, the lavatory is commonly used to express surprise as well as to identify the descriptive-evaluative function. Furthermore, the author discovered 5 of 10 subtitling strategies in this study, which included expansion, paraphrasing, transfer, condensation, and deletion. The transfer strategy is the most frequently used in translated taboo words, while expansion is the least frequently used.